Patterns of Refractive Errors in a Sample from Ibn Al Haytham Hospital, Baghdad, Iraq - Khaleel Hamdan, Safaa; Moravej, Raheleh; Khabazkhoob , Mehdi; Doostdar , Asgar (Journal of Ophthalmic and Optometric Sciences, 2025)
Purpose: To evaluate the patterns of refractive errors among patients who visited Ibn Al Haytham hospital, Baghdad, Iraq, from January 2023 to December 2023. Patients and Methods: This cross-sectional observational study was conducted between January 2023 and December 2023. Participants aged 18 and above were selected using random sampling from individuals referred for eye care at the hospital during the study period. Data were collected using a standardized checklist. Visual acuity tests with a Snellen chart, and refractive error measurements using an autorefractometer were performed. Results: Of the 309 participants included in the study, myopia was the most prevalent condition, affecting 63.8 % (n = 197), while hyperopia was present in 36.2 % (n = 112). Additionally, 40.1 % (n = 124) of participants had astigmatism, and 34.63 % (n = 107) had abnormal visual acuity. The distribution of refractive errors by gender showed that myopia (68.02 %, P = 0.001) and astigmatism (69.35 %, P = 0.016) were more prevalent in female participants. Job status was also associated with the distribution of refractive errors (P = 0.040) and astigmatism (P = 0.002). Finally, family history showed a significant association with the pattern of refractive errors among participants (P = 0.035). Conclusion: The study results highlight significant variations in the prevalence and patterns of refractive errors among patients at Ibn Al Haytham hospital, Baghdad, Iraq, with myopia being the most common condition. Gender, job type and familial history were found to have significant associations with different types of refractive errors.